Genomic analysis of Massilia antarctica subsp. insulae subsp. nov., a violacein- and aminochelin-producing bacterium isolated from Horseshoe Island, Antarctica - Sahin, Sibel Melisa; Saticioglu, Izzet Burcin; Duman, Muhammed; Sel, Sabriye; Ay, Hilal (SPRINGER, 2025)
Microorganisms isolated from polar regions are recognized for their considerable capability to encode unique proteins and metabolic pathways with importance for biotechnological applications. Specifically, microorganisms capable of generating pigments possessing antioxidant and antimicrobial properties as a strategy for survival amidst challenges like high ultraviolet radiation, low temperature, oxidative stress and microbial competition are noteworthy. In this research, we discovered a new subspecies of the species Massilia antarctica, designated as H27-R4T, which was isolated from a soil sample collected at Horseshoe Island in Antarctica. Strain H27-R4T is a purple-pigmented, rod-shaped, Gram-negative, and aerobic bacterium. Pairwise comparison of the 16S rRNA genes showed that the strain shares 100% identity with the type strain of Massilia antarctica P8398T and Massilia frigida CCM 8695 T, while the highest average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) values of 97.1% and 73.7%, respectively, were observed between strain H27-R4T and M. antarctica P8398T. The whole-genome analysis revealed a metabolic potential in terms of secondary metabolism, resistance to antimicrobials and heavy metals, adaptation to cold environments, stress response mechanisms and metabolism of aromatic compounds. In addition, the strain exhibited pathways for violacein and aminochelin biosynthesis. Phylogenomic analyses confirmed that strain H27-R4T represents a novel subspecies for which the name Massilia antarctica subsp. insulae subsp. nov. is proposed.
Keywords: Massilia; Violacein; Psychrophilic; Whole-genome analysis; Horseshoe Island; PIGMENTS; EXPRESSION; VIRULENCE; CREBC; Microbiology